HARMONIZATION OF SHARIA BUSINESS LAW AND POSITIVE LAW IN ZAKAT FUND MANAGEMENT AT LAZISMU GRESIK - Jefri Riskiyanda Saswito (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2026)
This study examines the normative and practical conflicts arising from the harmonization of Shariah and positive law in zakat fund management, using Lazismu Gresik as a case study. The objective is to identify implementation gaps between regulatory ideals and organizational practices. Through qualitative research involving 35 stakeholder interviews, the study reveals significant challenges in operationalizing Shariah compliance mechanisms, governance structures, and institutional autonomy under Law No. 23 of 2011. Key findings highlight: (1) the dual-role problem of BAZNAS as both regulator and operator, creating conflicts of interest; (2) shariah audit frameworks that remain predominantly administrative rather than substantive; and (3) difficulties in integrating Islamic principles with state law enforcement mechanisms. The research concludes that effective harmonization requires structural institutional reforms, strengthened substantive Shariah compliance mechanisms, and context-specific regulatory frameworks at the local level. This study contributes to understanding how legal pluralism can be operationalized in Islamic institutional contexts and provides practical recommendations for improving zakat governance.